Incidence of benign and malignant peri‐implant fluid collections and masses on magnetic resonance imaging in women with silicone implants. (30th September 2019) - Sutton, Elizabeth J.; Dashevsky, Brittany Z.; Watson, Elizabeth J.; Tyagi, Neelam; Bernard‐Davila, Blanca; Martinez, Danny; Dogan, Ahmet; Horwitz, Steven M.; Cordeiro, Peter G.; Morris, Elizabeth A.
Abstract: Background: To assess the incidence of benign and malignant peri‐implant fluid collections and/or masses on magnetic resonance imaging (MRI) in women with silicone implants who are being screened for silent implant rupture. Methods: The institutional review board approved this HIPAA‐compliant retrospective study and waived informed consent. Women who underwent silicone implant oncoplastic and/or cosmetic surgery and postoperative implant‐protocol MRI from 2000 to 2014 were included. Peri‐implant fluid collections and/or masses were measured volumetrically. A benign peri‐implant fluid collection and/or mass was pathologically proven or defined as showing 2 years of imaging and/or clinical stability. A malignant peri‐implant fluid collection was pathologically proven. Incidence of peri‐implant fluid collections and/or masses and positive predictive value (PPV) were calculated on a per‐patient level using proportions and exact 95% confidence intervals (CIs). Fisher's exact test was used in the analysis to test statistical significance pre‐defined as P ‐value < 0.05. Results: A total of 1070 women with silicone implants were included (mean age, 50.7 years; range, 40.4‐53.8). Median time between reconstructive surgery and first MRI was 88.9 months (range, 0.8‐1363.3). Eighteen women (1.7%) had a peri‐implant fluid collection and/or mass: 15/18 (83.3%) had adequate follow‐up; and only 1/15 was malignant implant associated anaplastic large cell lymphoma, with a PPV of 6.7% (95% CI: 0.003‐0.0005). The median peri‐implant fluid collection size was 89 mL (range, 18‐450 mL). Conclusion: Peri‐implant fluid collections and/or masses identified at silicone implant protocol breast MR imaging are rarely seen 24 months after reconstructive surgery. Image‐guided fine‐needle aspiration with flow cytometry may be warranted to evaluate for implant‐associated lymphoma. Abstract : Peri‐implant fluid collections and/or masses on implant protocol breast MRI are rarely seen 24 months after surgery. Image‐guided fine needle aspiration of delayed peri‐implant fluid collection may be considered, as there is a significant association with breast implant associated anaplastic large cell lymphoma.